2016
DOI: 10.12659/ajcr.900267
|View full text |Cite
|
Sign up to set email alerts
|

“REBOA” – Is it Really Safe? A Case with Massive Intracranial Hemorrhage Possibly due to Endovascular Balloon Occlusion of the Aorta (REBOA)

Abstract: Patient: Female, 86Final Diagnosis: PolytraumaSymptoms: ShockMedication: —Clinical Procedure: Resuscitative endovascular balloon occlusion of the aortaSpecialty: Orthopedics and TraumatologyObjective:Unusual or unexpected effect of treatmentBackground:Non-compressible torso hemorrhage continues to be the leading cause of preventable death in trauma patients. Recent case series report that resuscitative endovascular balloon occlusion of the aorta (REBOA) in the trauma population is a technically feasible method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 10 publications
2
46
0
2
Order By: Relevance
“…In a head and pelvic injury case treated by REBOA, Uchino et al . reported that a complication developed in the site proximal to the occlusion by REBOA in which minor intracranial bleeding was seen in the head CT at the initial diagnosis, wherein the bleeding suddenly increased and a cerebral hernia developed and the patient died [3]. In this case, REBOA excessively raised the perfusion pressure in the chest area proximal to the occlusion, and coagulopathy occurred, induced by trauma shock and trauma itself.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a head and pelvic injury case treated by REBOA, Uchino et al . reported that a complication developed in the site proximal to the occlusion by REBOA in which minor intracranial bleeding was seen in the head CT at the initial diagnosis, wherein the bleeding suddenly increased and a cerebral hernia developed and the patient died [3]. In this case, REBOA excessively raised the perfusion pressure in the chest area proximal to the occlusion, and coagulopathy occurred, induced by trauma shock and trauma itself.…”
Section: Discussionmentioning
confidence: 95%
“…However, complications developing around the site proximal to the occlusion, such as the possibility of increase in bleeding in the site proximal to the occlusion and the side effects of hyperperfusion, have hardly been studied to date. A systematic review [2] of REBOA, which included 61 articles and 1355 patients, showed that complications of the site proximal to the occlusion occurred only in one patient (0.07%) [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Although not addressed by this study, the effects of REBOA on the brain are not well characterized and may be similarly negatively impacted. Although increases in proximal flow and pressure from REBOA may exacerbate intracranial hemorrhage,30 the change in arterial impedance and capacitance may also adversely affect a non-injured brain. Similar to the effects on the heart, cases of hypertensive emergency with abrupt significant increases in afterload have been reported to result in encephalopathy, transient ischemic attack, and stroke 31.…”
Section: Discussionmentioning
confidence: 99%
“…We lack consensus on the use of REBOA in patients with concomitant TBI. Animal data have demonstrated a significant increase in intracranial pressure during occlusion, and case reports have documented worsening cerebral hemorrhage following REBOA [21][22]. Opinions regarding the use of REBOA in a polytrauma patient with TBI is mixed, with half of the providers identifying TBI as a contraindication for REBOA use.…”
Section: Reboa Techniquesmentioning
confidence: 99%